N-Glycosylation at Asn291 Stabilizes TIM-4 and Promotes the Metastasis of NSCLC - Chen, Siyuan; Wang, Yuzhen; Liu, Wen; Liang, Yan; Wang, Yingchun; Wu, Zhuanchang; Xu, Liyun; Liang, Xiaohong; Ma, Chunhong; Gao, Lifen (Frontiers in Oncology, 2022)
T-cell immunoglobulin domain and mucin domain 4 (TIM-4) is a transmembrane protein that promotes epithelial-mesenchymal transition (EMT), migration and invasion of non-small cell lung cancer (NSCLC) cells. Most transmembrane proteins are modified by N-glycosylation and the importance of protein N-glycosylation in cancer cell metastasis has been well appreciated. However, whether TIM-4 is modified by N-glycosylation and the role of TIM-4 N-glycosylation in NSCLC remains largely unknown. In the current study, we reported that TIM-4 was extensively N-glycosylated at Asn291. After the removal of N-glycosylation, the stability of TIM-4 protein was decreased and TIM-4 was more susceptible to degradation by ER-localized ubiquitin ligase-mediated ERAD. Thus, the expression of TIM-4 on the cell surface was decreased, which suppressed TIM-4-mediated metastasis in NSCLC. In summary, the present study identifies TIM-4 N-glycosylation and its role in NSCLS migration, which would provide a valuable biomarker for developing drugs targeting N-glycosylation at Asn291 on TIM-4.